SeV C Protein Plays a Role in Restricting Macrophage Phagocytosis by Limiting the Generation of Intracellular Double-Stranded RNA - Morita, Naoko; Tanaka, Yukie; Takeuchi, Kenji; Kitagawa, Yoshinori; Sakuma, Ryusuke; Koide, Naoki; Komatsu, Takayuki (Frontiers in Microbiology, 2022)
Macrophages play a central role in the innate immune response to respiratory viral infections through pro-inflammatory factor secretion and phagocytosis. However, as a countermeasure, viral pathogens have evolved virulence factors to antagonize macrophage function. In our recent in vitro analyses of murine macrophage cell lines, Sendai virus (SeV) accessory protein C inhibited the secretion of pro-inflammatory factors, and C gene-knockout SeV (SeV∆C) caused drastic morphological changes in RAW264.7 macrophages, similar to those observed after stimulation with Lipid A, a well-known activator of actin-rich membrane ruffle formation and phagocytosis. Hence, we sought to determine whether the C protein limits phagocytosis in SeV∆C-infected macrophages through the suppression of membrane ruffling. Phagocytosis assays indicated an upregulation of phagocytosis in both SeV∆C-infected and Lipid A-stimulated macrophages, but not in SeVWT-infected cells. Further, the observed membrane ruffling was associated with phagocytosis. RIG-I is essential for Lipid A-induced phagocytosis; its deficiency inhibited SeV∆C-stimulated phagocytosis and ruffling, confirming the essential role of RIG-I. Moreover, treatment with interferon (IFN)-β stimulation and neutralizing antibodies against IFN-β suggested that SeV∆C-induced phagocytosis and ruffling occurred in an IFN-β-independent manner. A newly isolated SeV∆C strain that does not generate dsRNA further highlighted the importance of dsRNA in the induction of phagocytosis and ruffling. Taken together, the current results suggest that SeV C protein might limit phagocytosis-associated membrane ruffling in an RIG-I-mediated but IFN-independent manner via limiting the generation of intracellular dsRNA.